DAMPAK KEBIJAKAN SUGAR TARIFF MEKSIKO TAHUN 2014 TERHADAP PERUSAHAAN COCA COLA ASAL AMERIKA SERIKAT - Siregar, Daniel Martua; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this study is to figure out the effectivity of sugary tariff done by Mexicoin 2014 on Coca Cola Company from the United States in case of the usage of High-FructoseCorn Syrup (HFCS) in Coca Cola soda that has increased mortality and obesity in Mexico, asthe background of this writing. Sugary Tariff policy issued by the Mexican government in 2014is a new policy to overcome the rate of circulation of soft drinks and to reduce the level ofconsumption as an attempt to avoid obesity.This study uses an Economic approach known as Mercantilism. There are two wellknownperspectives related in the study of International Political Economy: 1) the perspectiveof liberalism that offers free trade among countries in the world without any restriction in theform of tariff or non-tariff; and 2) the perspective of Mercantilism (economic nationalism)which is identical to protectionism.Protection strategy is a policy that is often used by a country to protect the nationalinterests especially by the affectuation of free market (Free Trade Area). Nowadays, Coca Colahas dominated 70% of the sales of soft drinks in Mexico and has affected Mexico's economicdevelopment. Hence, the enactment of sugary tariff in 2014 is a Mexican effort to protect theinterests of the country and it also has impacted to the Coca Cola Company.Kata Kunci : sugary tariff, HFCS , Kebijakan, Obesitas, Konsumtif, National Ekonomi,Merkantilis, Free Trade Area.